Knowledge, attitudes, and practices regarding dengue and its vectors among medical professionals: a cross-sectional study - Rania Ali El Hadi Mohamed; Yasir Khan; Khalid J. Alzahrani; Fuad M. Alzahrani; Khalaf F. Alsharif; Aamir Khan; Fazal Noor; Abdul Qadeer; Geng-Bai Lin; Chien-Chin Chen; Chien-Chin Chen; Chien-Chin Chen; et al. (Frontiers in Cellular and Infection Microbiology)
Dengue fever remains a significant global public health issue, necessitating a collaborative One Health strategy for efficient management. This cross-sectional study evaluated the knowledge, attitudes, and practices (KAP) of 516 healthcare professionals regarding dengue and its vectors. Most participants were young (82.6%), male (75.6%), and had MBBS qualifications (61.4%), predominantly employed in hospital settings (70.3%), and living in non-hotspot areas (53.3%). The research indicated that 65.1% of respondents possessed moderate knowledge about dengue, while 19.6% exhibited high knowledge and 15.3% showed low knowledge. Most participants (87.8%) correctly identified Aedes mosquitoes as the main vector, with 52.7% recognizing stagnant clean water as their breeding habitat. Positive attitudes were noted among 72.5% of participants; 51% viewed dengue as a moderately serious threat, and 47.3% strongly agreed on the crucial role of healthcare professionals in prevention. Conversely, 48.9% pointed out insufficient preventive measures in their facilities. In terms of practices, 80.8% of participants regularly informed patients about prevention, and 79.1% recommended CBC tests for suspected cases. Protective measures such as repellents and mosquito nets were consistently utilized by 57.2%, whereas 41.1% reported infrequent use. Remarkably, 59.7% had never undergone formal training on dengue prevention and management, with only 23.6% receiving consistent training. Furthermore, while 50.8% indicated that their facilities had adequate resources for dengue treatment, 42.8% reported a lack of mosquito control activities. These findings underline significant gaps in training, resource availability, and preventive practices, highlighting the urgent need for enhanced capacity-building, resource allocation, and intersectoral collaboration within the One Health framework to combat the effects of dengue in the region.